The boy on Fairfield Street : how Ted Geisel grew up to become Dr. Seuss - Krull, Kathleen; Johnson, Steve, 1960-; Fancher, Lou; Seuss, Dr. (New York : Random House, 2004)
Introduces the life of renowned children's author and illustrator Ted Geisel, popularly known as Dr. Seuss, focusing on his childhood and youth in Springfield, Massachusetts.
Includes bibliographical references (p. 43).
Wilson's Children.
School Library Journal starred.
Publisher's Weekly.
3.9
3-6
Keywords: Seuss, -- Dr. -- Childhood and youth -- Juvenile literature; Seuss, -- Dr. -- Childhood and youth; Seuss, -- Dr; Authors, American -- 20th century -- Biography -- Juvenile literature; Illustrators -- United States -- Biography -- Juvenile literature; Children's literature -- Authorship -- Juvenile literature; Authors, American; Illustrators; Authorship; American authors -- Biography; Illustrators -- Biography; Authorship; Authors, American -- Biography; Illustrators -- Biography; Authorship